Prevalence and antimicrobial susceptibility of bacterial isolates from horses with synovial sepsis: A cross-sectional study of 95 cases. (October 2016) - Robinson, C.S.; Timofte, D.; Singer, E.R.; Rimmington, L.; Rubio-Martínez, L.M.
Highlights: In this study, synovial sepsis was predominantly caused by a wound. Gram-positive bacteria were most frequently isolated. Single bacteria isolation was dominant. Antimicrobial sensitivity patterns provide antimicrobial selection advice. Oxytetracycline, trimethoprim–sulphamethoxazole and gentamicin are recommended. Abstract: Bacterial culture and antimicrobial susceptibility testing of septic synovial samples allows instigation of targeted antimicrobial therapy; however, bacterial culture takes more than 24 h and has low sensitivity. This study aimed to identify the most frequently cultured bacteria and their antimicrobial susceptibility profile from septic synovial samples in our referral equine hospital, to allow recommendations regarding appropriate initial antimicrobial therapy prior to culture results. Hospital records for all horses with synovial sepsis and a synovial sample submitted to the microbiology laboratory between 2004 and 2013 were retrieved ( n = 379 samples). One horse had positive cultures from more than one synovial structure, and two horses had positive cultures obtained from repeat samples. Overall, 114 bacterial isolates were obtained. Gram-positive bacteria were isolated in 75% of cases, of which 22% were haemolytic Staphylococcus spp., and 52% were Staphylococcus aureus including two multidrug-resistant isolates. Gram-negative bacteria were isolated from 25% of cases. Anaerobic Clostridium spp. was isolated in 3% of cases. Of the first line antimicrobials, oxytetracycline and doxycycline were effective against 70–100% of the Gram-positive bacteria and 20–100% of the Gram-negative organisms, whilst trimethoprim–sulphamethoxazole and gentamicin efficacy ranged between 50% and 88% for both Gram-positive and Gram-negative bacteria. Of the equine protected antimicrobials, ceftiofur was effective against 70–90% of all bacterial isolates whilst 80% of isolates were susceptible to enrofloxacin. These results indicate that tetracyclines, trimethoprim–sulphamethoxazole or gentamicin may be suitable first-line antimicrobials for treatment of synovial sepsis cases while awaiting laboratory results, findings which support current recommendations for antimicrobial stewardship in equine medicine.